2008
DOI: 10.1051/pmed:2008332
|View full text |Cite
|
Sign up to set email alerts
|

Le vécu des dissections au laboratoire d'anatomie. Conséquences psychologiques et actions pédagogiques

Abstract: Mots clés :Cadavre ; laboratoire d'anatomie ; dissections, étudiant(e)s en médecine ; infirmier(e)s de bloc opératoire Résumé -Contexte : Les travaux pratiques de dissections sont toujours l'objet de réactions particulières avant, pendant ou après la rencontre avec les cadavres. But : Mieux comprendre dans une perspective comparative ce qui se passe chez les jeunes étudiant(e)s de seconde année de médecine qui sont souvent vierges de toute expérience de la mort et chez des étudiant(e)s infirmier(e)s de bloc op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
2
0
2
Order By: Relevance
“…Among doctors in training, autopsy definitely constitutes an initiation rite that leaves an indelible impression on the psyche and usually takes the subject by surprise. Several studies carried out among medical students reveal the intensity of the affects that are unfailingly aroused by dissecting a corpse (Bonnaud-Antignac et al, 2008). Whether or not this is a first encounter with death, the autopsy induces a sense of physical and psychic unease, an intense anxiety, connected less with the mere sight of the dead person -autopsy is more than this vision -than with cutting up and opening the corpse.…”
Section: Autopsy As a Revelationmentioning
confidence: 99%
“…Among doctors in training, autopsy definitely constitutes an initiation rite that leaves an indelible impression on the psyche and usually takes the subject by surprise. Several studies carried out among medical students reveal the intensity of the affects that are unfailingly aroused by dissecting a corpse (Bonnaud-Antignac et al, 2008). Whether or not this is a first encounter with death, the autopsy induces a sense of physical and psychic unease, an intense anxiety, connected less with the mere sight of the dead person -autopsy is more than this vision -than with cutting up and opening the corpse.…”
Section: Autopsy As a Revelationmentioning
confidence: 99%
“…Plus rares sont les réflexions et les analyses qui s'interrogent sur le vécu de ceux et de celles qui traversent ces apprentissages-initiations. Aussi, la contribution d'Angélique Bonnaud-Antignac et de ses collaborateurs, qui paraît dans ce numéro, doitelle être examinée avec un intérêt particulier [2] .…”
Section: Voir Savoir Et Devenir Médecinunclassified
“…De la capacité à voir et voir beaucoup, dépend la valeur d'un médecin expérimenté. En effet, Claude Bernard note déjà au milieu du XIX e siècle « qu'on n'arrivera jamais à des généralisations fécondes et lumineuses sur les phénomènes vitaux qu'autant qu'on n'aura expéri-menté soi-même et remué dans l'hôpital, l'amphithéâtre ou le laboratoire, le terrain fétide et palpitant de la vie » [2] .…”
Section: Voir Savoir Et Devenir Médecinunclassified
“…There is a considerable literature to suggest that, at least initially, some medical students may be emotionally disturbed by the prospect of being in the dissecting room (Becker et al, ; Lief and Fox, ; McGuire, ; Shalev and Nathan, ; Harvill, ; Jordan et al, ; Finkelstein and Mathers, ; Horne et al, ; Evans and Fitzgibbon, ; Druce and Johnsons, ; Lee‐Tsang‐Tan and Kent, ; Abu‐Hijleh et al, ; Dickinson et al, ; Nnodim, ; Tschernig et al, ; Dinsmore et al, ; O'Carroll et al, ; Snelling et al, ; Hancock et al, ; Houwink et al, ; Arráez‐Aybar et al, , , ; Bonnaud‐Antignac et al, ; Schwartz et al, ; Cahill and Ettarh, ; Plaisant et al, , ; Boeckers et al, ; Leboulanger, ; Limbrecht et al, ; Martyn et al, ; Williams et al, ; Wei‐Ting and Ya‐Ping, ; Boeckers and Boeckers, ). Indeed, it has even been suggested that teaching students using cadavers might be considered “unethical” (McLachlan et al, ; McLachlan and Patten, ).…”
Section: Introductionmentioning
confidence: 99%